Effects of static electric fields on growth and development of wheat aphid Sitobion aveanae (Hemiptera: Aphididae) through multiple generations. (2nd January 2016) - He, Juan; Cao, Zhu; Yang, Jie; Zhao, Hui-Yan; Pan, Wei-Dong
Abstract: Insects show a variety of responses to electric fields and most of them are associated with immediate effects. To investigate the long-term effects of static electric field on the wheat aphid Sitbion avenae, the insert was exposed to 4 min of a static electric field at intensities of 0, 2, 4, or 6 kV/cm. Development effects over 30 consecutive generations of the insect were studied. The results showed that the electric field could exert adverse effects on the developmental duration and total longevity of S. avenae nymphs regardless of exposure intensities or generations. The effects appeared to be more intense and fluctuated at higher electric field intensities and more insect generations. The most favorable exposure for development was 6 kV/cm for 4 min while the most detrimental electric fields were 2 kV/cm for 4 min and 4 kV/cm for 4 min. Among the treatments, the first instar duration was significantly prolonged while the adult longevities were significantly shortened in the sixth generation. The intrinsic rate of increase and net reproductive rate in the sixth generation were also the lowest among the 30 consecutive generations studied. Based on the results, the adverse effects of electric fields on insects may be used in the bio-control of pest insects in terms of pest management.